Analysis of the Financial Performance of the Jawa Tengah Provincial Government For The 2020-2024 Fiscal Years Based on Independence, Effectiveness, Efficiency, Harmony, Growth, and Activity Ratios and Their Implications For Regional Fiscal Governance - Muhammad Fadhli Siregar; Anggi Pratama Nasution; Galih Supraja (Journal of Research in Social Science and Humanities, 2025)
This study aims to examine the financial performance of the Jawa Tengah Provincial Government during the 2020-2024 period by considering the impacts of the COVID-19 pandemic and the leadership transition that occurred in 2023. The analysis employs a quantitative descriptive approach using data from the Budget Realization Reports and evaluates performance through six financial ratios, namely independence, effectiveness, efficiency, harmony, growth, and activity ratios. The findings indicate that the independence ratio is classified as moderate with an upward trend, while the effectiveness ratio remains in the highly effective category throughout the observation period. Conversely, the efficiency ratio declined and reached an inefficient level in 2023-2024 due to increased expenditure related to economic recovery efforts. The harmony ratio reveals the continued dominance of operational expenditures within the regional budget structure, whereas fiscal growth fluctuated but showed signs of stabilization toward the end of the period. In addition, the activity ratio falls into a very high category, reflecting strong regional fiscal capacity. Overall, the financial performance of Jawa Tengah Province can be considered stable and adaptive to external challenges; however, improvements in efficiency and the allocation of more productive expenditures are still required to support long-term fiscal sustainability